The effects of sintering additives on the mechanical properties and microstructure evolution of 3 MOL% Y-TZP / Nur Nadia Ahmad Hasan - Nur Nadia, Ahmad Hasan (2017)
3mol% Yttria stabilized Tetragonal Zirconia Polycrystalline (3Y-TZP) ceramic is one of the most demanding material in biomedical application because it possesses the best combination of mechanical properties, biocompatibility and aesthetic properties. These extraordinary properties were attributed to its transformation toughening mechanism as it provides resistance to crack propagation by externally applied stress as a consequence of phase transformation from tetragonal(t) to monoclinic(m) at room temperature. One major drawback with use of the zirconia is the significant loss in mechanical properties attributed by undesired transformation phase tetragonal to monoclinic(tm) when undergo ageing or low temperature degradation(LTD). The current work investigates the effects of sintering additives, particularly focused on 0.5 wt% manganese oxide (MnO2) and 0.1 wt% alumina (Al2O3), and co-doping both additives together (i.e. MnO2 + Al2O3), on the microstructure and mechanical properties of 3 mol% Y-TZP. The doped powders were prepared by attrition milling and subsequently green samples were sintered in air at temperatures ranging from 1250℃ to 1550°C with 2 hours holding time. The results showed that the dopants have not disrupted the tetragonal phase stability. All the dopants aided sintering at 1250°C but with MnO2 being most effective in promoting densification with samples, recording about 97.6 % relative density. Similar improvement in the mechanical properties was also observed for the doped zirconia. Young’s modulus, Vickers hardness and fracture toughness as high as 192 GPa, 13.6 GPa and 4.6 MPam1/2, respectively were obtained for both, the MnO2-doped and co-doped Y-TZPs, when sintered at low temperature of 1250°C. Microstructural examinations however revealed that the MnO2 dopant promoted exaggerated grain growth when sintered at higher temperatures. In addition, the study also found that LTD phenomena in superheated steam condition was suppressed when average grain size not exceed 0.32 μm, particularly for samples sintered at lower temperature.